PKM Penguatan Pedagogik Pendidik Paud Dalam Pengembangan Modul Ajar Berbasis Kearifan Budaya Lokal Di Kota Medan - Simatupang, Eli Verawati; Fitriyani; Siregar, Nurhelan; Ajat (JURNAL BUNGA RAMPAI USIA EMAS, 2025)
This community service activity (PKM) aims to increase pedagogical competency of Early Childhood Education teachers (PAUD) in Medan City in developing local cultural wisdom based teaching modules. As one of the major cities in Indonesia, Medan has a cultural diversity that needs to be preserved and introduced early to children. But many Paud teachers had difficulty integrating local culture into learning. It was designed with a variety of learning methods, including lectures, debriefing, discussions, and evaluation, to provide teachers with an understanding of the importance of the introduction of local culture in early childhood education. Participants made up of 20 PAUD teachers participated in training that included local culture-based PAUD understanding, local cultural mapping, and how to design local cultural-based teaching modules. The pretest result showed a limited initial understanding, while the posttest result showed a significant increase in participants' understanding of the material taught. The program proved effective in improving teacher competencies and supported the preservation of local culture in early childhood education.